The clinical significance of patients' sex in chronic lymphocytic leukemia. - Catovsky, D; Wade, R; Else, M (2014)
We examined the prognostic influence of gender in chronic lymphocytic leukemia. Data from four randomized trials (involving 1821 patients) and three registration studies of stage-A disease (involving 1299 patients) were analyzed. Overall survival at 10 years was better for women than men in all trials (27% versus 15%; P=0.0001) and in the registration series (55% versus 43%; P<0.0001). More women than men in the trials were Binet stage A-progressive (26% versus 15%), but gender was an independent predictor of survival in multivariate analysis of clinical variables (P<0.0001). Women responded better to treatment (overall response 83%) than men (71%; P<0.0001), within each stage and age group, although fewer women than men received the full treatment dose (79% versus 85%; P=0.01). Women were more likely than men to experience toxicity (85% versus 78%, P=0.01), particularly gastro-intestinal toxicity (57% versus 42%, P<0.0001). Laboratory markers in the LRF CLL4 trial showed a significantly lower incidence in women than men of unmutated IGHV genes, raised beta-2 microglobulin, CD38 and Zap-70 positivity and TP53 deletions/mutations and/or 11q deletions. We also highlight the higher male:female ratios in randomized trials versus studies of early chronic lymphocytic leukemia and monoclonal B-cell lymphocytosis. Chronic lymphocytic leukemia in women runs a more benign clinical course than in men. Gender was also an independent predictor of response, suggesting that pharmacokinetic differences between the sexes and a possible effect of estrogens may contribute to the better outcome. Understanding the reasons for the different outcome by gender may improve patients' management. (LRF CLL4 controlled-trials.com identifier: ISRCTN58585610).